الأحاديث التي ورد فيها لفظ "خصلتان" عن النبي "صلى الله عليه وسلم": جمعا وتخريجا ودراسة - الرشيدي، عواطف بنت نصار بن علي (جامعة أم القرى, 2021)
I have collected in this study the hadiths in which the expression: "Two characteristics..." was mentioned on the authority of the Prophet. Hurairah, Abdul Rahman bin Auf, Abu Saeed Al Khudri, Salman Al Farsi, Khuraim bin Fatak, Mazidah bin Jaber, Mursal Ziyad bin Abi Ziyad, and Abu Qilabah Al Jurimi. I have studied all these hadiths, and explained the difference in the chain of transmission that occurred in them, and mentioned the degree of each hadith and its judgment, relying on the sayings of the critics of the imams, and a memory of what was found to me by looking at these hadiths, and I also mentioned the strange hadith as required by the words. Strange, and concluded each authentic hadith with a set of benefits. And Allah is the Grantor of success.
جمعت في هذا البحث الأحاديث التي ورد فيها لفظ: (خصلتان) عن النبي صلي الله عليه وسلم، وقد وقفت على ستة عشر حديثا في ذلك، وهي: حديثا عبدالله بن عمرو، وأنس بن مالك، وعبدالله بن عباس، وعبدالله بن عمر، وحديث أبي هريرة، وعبدالرحمن بن عوف، وأبي سعيد الخدري، وسلمان الفارسي، وخريم بن فاتك، ومزيدة بن جابر، ومرسل زياد بن أبي زياد، وأبي قلابة الجرمي. وقد درست جميع هذه الأحاديث، وبينت ما وقع فيها من اختلاف في الإسناد، وذكرت درجة كل حديث، والحكم عليه، معتمدة على أقوال الأئمة النقاد، وذاكرة ما تبين لي من خلال النظر في هذه الأحاديث، كما أنني ذكرت غريب الحديث فيما تطلب ذلك من الكلمات الغريبة، وختمت كل حديث صح بجملة من الفوائد. وبالله التوفيق.
Keywords: علم الأحاديث -- محمد، صلى الله عليه وسلم، ت. 11 هـ. -- لفظ "خصلتان" -- المسائل الدينية